2018
DOI: 10.1787/d8c0fbc4-en
|View full text |Cite
|
Sign up to set email alerts
|

Basic income or a single tapering rule? Incentives, inclusiveness and affordability compared for the case of Finland

Abstract: OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcomed, and may be sent to the Economics Department,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Microsimulation has shown that previously proposed universal benefits for Ireland can have detrimental consequences for some low earners. Pareliussen et al (2018) show that a similar type of UBI for Finland could lead to an increase in income inequality and conclude that the existing targeted benefit system does a better job. Hanna and Olken (2018) provide comprehensive discussion and analysis of the role of UBI versus targeted transfers at reducing poverty in developing countries.…”
Section: Section 2 Ubi Policy In Ireland: 30 Years Of Policy Discussi...mentioning
confidence: 92%
See 1 more Smart Citation
“…Microsimulation has shown that previously proposed universal benefits for Ireland can have detrimental consequences for some low earners. Pareliussen et al (2018) show that a similar type of UBI for Finland could lead to an increase in income inequality and conclude that the existing targeted benefit system does a better job. Hanna and Olken (2018) provide comprehensive discussion and analysis of the role of UBI versus targeted transfers at reducing poverty in developing countries.…”
Section: Section 2 Ubi Policy In Ireland: 30 Years Of Policy Discussi...mentioning
confidence: 92%
“…A UBI may be poorly targeted, as a large percentage of recipients will be highearning individuals. Pareliussen et al (2018) used microsimulation to evaluate the impacts of implementing a fiscally-neutral UBI in Finland. While that payment is quite modest, being roughly similar to the rate of jobseeker's benefit in Finland, it requires substantial income tax increases along with a removal of certain benefits.…”
Section: Introduction|3mentioning
confidence: 99%
“…An in-depth study for Finland using micro-simulation is quite instructive about what basic income does and how it compares to an alternative approach of providing minimum income protection in the shape of a universal credit, similar to what exists in the UK (Pareliussen et al, 2018).…”
Section: What We Know About the Impact Of Basic Income On Poverty And...mentioning
confidence: 99%
“…The study by Pareliussen et al (2018) compares Finland's benefit system with two benefit reform scenarios: a uniform benefit for all ("basic income") and a universal tapering rule ("universal credit"). It finds that replacing current benefits with a basic income would improve work incentives for many, but it would involve a drastic redistribution of income and an increase in poverty.…”
Section: What We Know About the Impact Of Basic Income On Poverty And...mentioning
confidence: 99%
“…Cela limiterait aussi les coûts de gestion de ces dispositifs en uniformisant les bases de calcul. Cependant, l'expérience du Royaume-Uni montre que la mise en oeuvre d'une telle réforme est complexe et demande des changements majeurs dans les pratiques institutionnelles (Pareliussen et al, 2018 ;Encadré 9).…”
Section: B Le Marché Du Logement Contribue Au Mésappariement Des Compétencesunclassified